The Correlation Between Preeclampsia and the Incidence of Low Birth Weight (LBW) in Rsu PKU Muhammadiyah Bantul - Sholaikhah Sulistyoningtyas; Nur'aisyah Nur'aisyah (Universitas 'Aisyiyah Yogyakarta, 2020)
MMR and IMR in the world as well as in Indonesia are still a serious problem because this figure is an indicator of national health. The common cause of infant and neonatal mortality in Bantul Regency is low birth weight (LBW). One of the factors causing LBW is maternal disease factors that are directly related to pregnancy. One of them is preeclampsia. The purpose of this study was to determine the Correlation between Preeclampsia and the Incidence of Low Birth Weight Infants (LBW) at PKU Muhammadiyah Bantul Hospital in 2019. The design of this study used the correlation analytical method with a case control approach. The sampling method in this study used total sampling technique with the total sample size of the study were 174 newborns. The data collection technique used secondary data by collecting baby medical record data and maternal medical record data. The analysis technique used the chi square test. Babies who experienced LBW were as many as 87 (50%), did not experience LBW as many as 87 (50%), those who had preeclampsia were 45 (25.9%), did not experience preeclampsia as many as 129 (74.1%). The results of the study based on the chi square test showed that there was no correlation between preeclampsia and the incidence of low birth weight (LBW) with p = 0.863 and an odds ratio of 0.942. The conclusion is that there is no correlation between preeclampsia and the incidence of low birth weight babies (LBW), the p value is 0.863 0.05. It is suggested that further analysis of other maternal factors on the incidence of low birth weight in PKU Muhammadiyah Bantul Hospital.